Realisation of a thermoformed vibro-acoustic metamaterial for increased STL in acoustic resonance driven environments. (15th December 2019) - de Melo Filho, N.G.R.; Claeys, C.; Deckers, E.; Desmet, W.
Abstract: This paper discusses the design and validation of a thermoformed locally resonant metamaterial panel tuned to attenuate the excitation of the first acoustic mode of a cavity. Moreover, it brings resonant metamaterials closer to industrial realisations by exploiting a cheap and widely used production process. The concept is explained, and it is shown how the stop band can be tuned to a targeted frequency. Additionally, multiple stop bands are achieved by combining two differently tuned locally resonant parts in the same metamaterial panel. The proposed thermoformed metamaterial panels have similar weight as the original panel and superior experimentally evaluated insertion loss performance in the frequency range of the stop band.